2019
DOI: 10.3390/socsci8010011
|View full text |Cite
|
Sign up to set email alerts
|

Putting Research to Action: Integrating Collaborative Governance and Community-Engaged Research for Community Solar

Abstract: Community solar involves the installation of a solar electricity system that is built in one central location with the costs and benefits distributed across voluntary investors who choose to subscribe and receive credits based on the generated energy. Community solar is gaining attention because of its potential to increase access to renewable energy and to democratize energy governance. This paper reflects on community-engaged research experiences in two rural community case studies in Michigan, USA, focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The techno-economic feasibility of 100% or nearly 100% RE transition in the United States have been studied by various researchers [16][17][18]. Previous studies have captured public and stakeholder perceptions on solar projects [9,19], while other studies have shown the engagement of individuals on various wind projects [20]. One of the explanations for the dearth in this research area is the relatively new concept of 100% RE in the United States and the very few empirical case studies in this context.…”
Section: Public Perception Of 100% Renewable Electricity In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The techno-economic feasibility of 100% or nearly 100% RE transition in the United States have been studied by various researchers [16][17][18]. Previous studies have captured public and stakeholder perceptions on solar projects [9,19], while other studies have shown the engagement of individuals on various wind projects [20]. One of the explanations for the dearth in this research area is the relatively new concept of 100% RE in the United States and the very few empirical case studies in this context.…”
Section: Public Perception Of 100% Renewable Electricity In the United Statesmentioning
confidence: 99%
“…For instance, the Western UP Planning and Development Region (WUPPDR) has renewable energy deployment as part of its plans [44]. In 2018, the WUPPDR requested the assistance of researchers from the University of Michigan (UM) and Michigan Technological University (MTU) to carry out technical and cost-benefit analyses for community solar in the Keweenaw Bay Region [40], resulting in a community solar project [19,40,44,45]. While techno-economic analysis is important in this process, the opinions of the public who are at the center of this energy development are equally germane.…”
Section: Electricity Price and Environmental Concern In The Case Of Michigan's Western Upper Peninsulamentioning
confidence: 99%
“…Local embeddedness is another benefit in community energy initiatives. CECs focus on the local community in their actions related to sustainable developments (Prehoda, Winkler, & Schelly, 2019). Especially in the UK, as per the Community Benefit Society Act of 2014, CECs are required to re-invest their profits into the local community to support sustainable developments.…”
Section: Roles and Motivesmentioning
confidence: 99%
“…2021;3(1):e210004. https://doi.org/10.20900/jsr20210004 [190]-may be particularly well suited for collaborative governance [191],…”
Section: Researchers and Practitioners Who Met At The Energy Democracymentioning
confidence: 99%
“…given that it necessitates cooperation among its participants. Some lessons that have been learned about community-solar participants are that they want local control over their energy, strong financial incentives, inclusivity for those with low incomes, environmental sustainability, assurance of long-term solar maintenance, and mutual trust between them and those who initiate the PV project [191]. Of course, collaborative governance on energy issues can fail when the participants themselves fail to agree on a procedural outcome [173], which may be an effect of renewable energy's status as a politically contentious issue in the United…”
Section: Researchers and Practitioners Who Met At The Energy Democracymentioning
confidence: 99%